Teaching handball to U-16 and U-18 women’s teams: coaches’ perspective on the long-term - Menezes,Rafael Pombo (2018)
Abstract Aims: To identify the teaching approaches preferred by Brazilian coaches in the U-16 and U-18 women’s teams and whether it is possible to apply long-term goals for handball training. Methods: Six experienced coaches were interviewed individually in a semi-structured format. Data were transcribed and analyzed according to the Collective Subject Discourse (CSD) method. Results: Coaches revealed a choice for the situational approach and global-functional approach in U-16 teams. In U-18 teams, coaches’ choices were for the technique and situational approaches. The change of coaches’ choice might be based on players’ specialization, suggested to U-18 teams when coaches highlighted the increased demand for performance. On players’ transition from U-16 to U-18 teams, the coaches showed less preference for the global-functional approach and increasing evidence of the technique approach. Conclusion: Global-functional and situational approaches should be given a prominent position in these teams, especially due to the development of technical-tactical aspects. However, the technical approach was recognized as a central position in U-18 teams, probably related to players’ specialization and technical improvement, although it does not offer a rich environment for the development of players’ decision making.